Power sharing in deeply divided places - McEvoy, Joanne; O'Leary, Brendan (National and ethnic conflict in the 21st century., 2013)
This volume considers an array of power-sharing systems in divided cities and states, with critical evaluations of their merits and defects as well as explanations of their emergence, maintenance, and failings.